(untitled) (Diversity Research: Journal of Analysis and Trends, 2025)
Content-Based Learning (CBL) is an educational approach that integrates subject-specific content with language learning, emphasizing the acquisition of knowledge through the context of real-world materials. This article explores how Content-Based Learning plays a crucial role in developing reading comprehension skills, examining theoretical frameworks, educational practices, and empirical studies. Through an analysis of various teaching models and their practical applications, the article argues that CBL not only enhances students’ ability to understand written text but also deepens their engagement with content across disciplines.